(untitled) - Ross, Alan (Philippines, 2005)
This report summarizes the actions that are required to address road safety in the region. The report suggests that, if the measures are successfully implemented over the next 5 years, they would save 42,000 lives, result in lesser injuries to 3 million individuals, and reduce economic losses by more than
Keywords: Traffic safety,An toàn giao thông